KEWENANGAN PENGADILAN YANG DIPILIH DALAM KLAUSULA PILIHAN PENGADILAN: TINJAUAN BERDASARKAN HUKUM PERDATA INTERNASIONAL INDONESIA - Afifah Kusumadara (Veritas et Justitia, 2025)
A choice of court agreement made by contracting parties is recognized under Indonesian civil procedure law. Nevertheless, Indonesian courts frequently decline to uphold the jurisdiction of the court selected by the parties. This is because, under Indonesian Civil Procedure Rules, the principle of actor sequitur forum rei may take precedence over the parties’ choice of court agreement. Moreover, as Indonesian law does not expressly regulate the jurisdiction of foreign courts, Indonesian courts tend to assert jurisdiction over disputes even where the parties have nominated a foreign court in their agreement. This article is based on normative juridical research involving the analysis of legal materials consisting of statutes and regulations, case law, and legal doctrine. In light of these findings, the article proposes that Indonesia enact the Bill on Private International Law, which includes provisions governing international jurisdiction for both Indonesian and foreign courts. Additionally, the article advocates for Indonesia’s accession to the 2005 Hague Convention on Choice of Court Agreements and outlines recommended measures to safeguard Indonesia’s national interests through reformation of the judiciaries.